A nova Grammatica de língua Franceza (1831) de Francisco Solano Constâncio à luz da gramaticografia francesa contemporânea - Rolf Kemmler; Natália Amarante; Teresa Moura; Maria Luísa de Castro Soares (Carnets)
In 1831, the Portuguese-born physician Francisco Solano Constâncio (1777-1846) published in Paris two metalinguistic works for a Lusophone public. Alongside the Grammatica analytica da lingua portugueza (Constâncio, 1831b), the Nova grammatica da lingua franceza (Constâncio, 1831a) is of special interest to the history of the French metalinguistic tradition and the history of French language teaching in Portugal, since the author identifies its possible source on the title page of his work. Therefore, the present paper offers an analysis of the initial description of the parts of the speech in the Nova grammatica da lingua franceza in light of the Nouvelle grammaire française, sur un plan très-méthodique, an important contemporary metalinguistic work by the French grammarians François-Joseph-Michel Noël (1756-1841) and Charles-Pierre Chapsal (1787-1858) which by then already had twenty editions since 1823.